PENERAPAN TERAPI SLEEP HYGIENE PADA ANAK USIA PRASEKOLAH YANG MENGALAMI GANGGUAN POLA TIDUR SAAT HOSPITALISASI DI RUANG SALMANAL-FARISI RSU ASRI PURWAKARTA - Wirdan Fauzi Rahman; Yuli Erlina; Susanti Adiningrum (LPSDI Bina Patria, 2025)
Sleep disturbances are common among preschool-aged children during hospitalization. Environmental changes, bright lights, noise, and feelings of fear or anxiety can lead to difficulty sleeping or poor sleep quality. One of the non-pharmacological interventions to improve sleep patterns is sleep hygiene therapy. Objective: To determine the effect of implementing sleep hygiene therapy on the sleep patterns of preschool children experiencing sleep disturbances during hospitalization at Salman Al-Farisi Ward, RSU Asri Purwakarta. This study used a pre-experimental design with a pretest-posttest approach without a control group. The total sample consisted of 30 children aged 3–6 years who met the inclusion criteria. Data were collected using a sleep observation sheet and sleep hygiene checklist. Data were analyzed using the Wilcoxon Signed Rank Test. Result: Before the intervention, most children had poor sleep patterns (66.7%), while after the intervention, 60% were in the good category. The Wilcoxon test showed a p-value = 0.000 (< 0.05), indicating a significant difference between pre- and post-intervention sleep patterns. Conclusion: Sleep hygiene therapy effectively improves the sleep patterns of hospitalized preschool children by establishing consistent bedtime routines, creating a comfortable environment, and involving parental participation